2014
DOI: 10.1542/peds.2013-1794
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sodium, Adiposity, and Inflammation in Healthy Adolescents

Abstract: WHAT'S KNOWN ON THIS SUBJECT: High sodium intake is considered an indirect cause of obesity because it is often accompanied by higher energy intake and sugar-sweetened soft drink consumption. High sodium intake is associated with increased inflammatory response in adult patients. WHAT THIS STUDY ADDS:This study shows that high sodium intake is positively associated with adiposity, leptin, and tumor necrosis factor-a independent of total energy intake and sugarsweetened soft drink consumption in healthy white a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
119
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(141 citation statements)
references
References 44 publications
15
119
1
3
Order By: Relevance
“…Earlier studies reported that dietary sodium intake was associated with body size including body weight, BMI, and overweight, 7,8 and additional evidence has suggested that increased sodium intake could alter markers for inflammation responses. 12,29 In the current study, however, dietary sodium intake did not show a significant influence on body weight, BMI, percent body fat, visceral fat area, or waist or hip circumference, and these insignificant associations held even when we considered total energy and dietary intake and lifestyle factors. These limited associations could have resulted from the obesity levels of the study participants.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Earlier studies reported that dietary sodium intake was associated with body size including body weight, BMI, and overweight, 7,8 and additional evidence has suggested that increased sodium intake could alter markers for inflammation responses. 12,29 In the current study, however, dietary sodium intake did not show a significant influence on body weight, BMI, percent body fat, visceral fat area, or waist or hip circumference, and these insignificant associations held even when we considered total energy and dietary intake and lifestyle factors. These limited associations could have resulted from the obesity levels of the study participants.…”
Section: Discussioncontrasting
confidence: 75%
“…10,11 Furthermore, although there are inconsistencies, dietary sodium intake was associated with body mass index (BMI) and overweight. 7,12 This suggests that dietary sodium plays an intricate physiological role in obesity as well as human metabolism. Recent studies reported that excess sodium intake may affect innate immunity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the traditionally recognised health effects of high Na intake, obesity has recently gained much interest as another possible related health outcome (5) . Although several studies including a longitudinal study have reported significant associations between Na intake and obesity among adults (9)(10)(11)(12)(13)(14) , relatively limited evidence is available among children and adolescents (15)(16)(17)(18) . Investigation of the associations between Na intake and obesity, however, has been limited by weakness of assessment methods of both Na intake and obesity.…”
mentioning
confidence: 99%
“…(32) relacionan un consumo elevado de sal de manera indirecta con el exceso de peso, otros estudios como los de Zhu y cols. (33) han encontrado una asociación positiva entre una alta ingesta de sodio y varias medidas de la obesidad como: el peso, la circunferencia de la cintura, el porcentaje de grasa corporal, entre otros indicadores. Por lo tanto, teniendo en cuenta la evidencia antes mencionada determinamos que las DN relevantes para la prevención de la obesidad son las relativas a las grasas, especialmente las saturadas (34,35), los azúcares, la fibra alimentaria y la sal.…”
Section: Discussionunclassified